Technological Surveillance of Communication in American, German and Chinese Criminal Procedure. - Shi, Jiahui (Duncker & Humblot, 2022)
Due to the rise of organized crime and the rapid development of surveillance technologies, such technologies are increasingly used for the purpose of criminal investigation. However, the proliferation of such highly intrusive measures can jeopardize the individual right to privacy and the constitutionally protected secrecy of private telecommunication. It is therefore necessary to devise a legal framework that balances the need for efficient law enforcement with individuals' privacy rights. In this study, the author discusses the laws on covert surveillance as an investigative measure in the criminal process of the United States, Germany, and the P.R. China from theoretical and empirical perspectives. The author then provides a horizontal comparison of the three legal systems, with the aim of identifying solutions that achieve a proper balance between the protection of the right to privacy and the effective combat of crime.Due to the rise of organized crime and the rapid development of surveillance technologies, such technologies are increasingly used for the purpose of criminal investigation. However, the proliferation of such highly intrusive measures can jeopardize the individual right to privacy and the constitutionally protected secrecy of private telecommunication. It is therefore necessary to devise a legal framework that balances the need for efficient law enforcement with individuals' privacy rights. In this study, the author discusses the laws on covert surveillance as an investigative measure in the criminal process of the United States, Germany, and the P.R. China from theoretical and empirical perspectives. The author then provides a horizontal comparison of the three legal systems, with the aim of identifying solutions that achieve a proper balance between the protection of the right to privacy and the effective combat of crime.
Description based upon print version of record.
a) The Scope of the Exclusionary Rule under Title III
Keywords: Electronic surveillance -- Law and legislation -- United States.; Electronic surveillance -- Law and legislation -- Germany.; Electronic surveillance -- Law and legislation -- China.; Electronic surveillance -- Law and legislation; China; Germany; United States